2019
DOI: 10.1152/japplphysiol.00023.2019
|View full text |Cite
|
Sign up to set email alerts
|

Separate and combined influences of heat and hypobaric hypoxia on self-paced aerobic exercise performance

Abstract: Heat and hypobaric hypoxia independently compromise exercise performance; however, their combined impact on exercise performance has yet to be quantified. This study examined the effects of heat, hypobaric hypoxia, and the combination of these environments on self-paced cycling time trial (TT) performance. Twelve subjects [2 female, 10 male; sea level (SL) peak oxygen consumption (V̇o2peak), 41.5 ± 4.4 mL·kg−1·min−1, mean ± SD] completed 30 min of steady-state cycling exercise (50% SL V̇o2peak), followed by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…However, in H+H, muscle and skin temperatures reached 38.1 ± 0.1 • C and 36.2 ± 0.2 • C, respectively, by the end of exercise. These levels are comparable with those observed in previous studies, reporting skin temperatures of approximately 35 • C during exercise under 35 • C (Bradbury et al, 2019). We also evaluated muscle oxygenation because previous studies reported that lower muscle oxygenation (increased muscle deoxygenation) may aggravate the accumulation of exercise-induced metabolites (Grassi et al, 1999).…”
Section: Discussionsupporting
confidence: 81%
“…However, in H+H, muscle and skin temperatures reached 38.1 ± 0.1 • C and 36.2 ± 0.2 • C, respectively, by the end of exercise. These levels are comparable with those observed in previous studies, reporting skin temperatures of approximately 35 • C during exercise under 35 • C (Bradbury et al, 2019). We also evaluated muscle oxygenation because previous studies reported that lower muscle oxygenation (increased muscle deoxygenation) may aggravate the accumulation of exercise-induced metabolites (Grassi et al, 1999).…”
Section: Discussionsupporting
confidence: 81%
“…Variables including heart rate and ventilation have been shown to be related to RPE during exercise (1). Our recent work in simulated altitude (7) suggests that individuals titrate their work rate during self-paced TT exercise based on physiological feedback such as HR and RPE to maintain an optimal exercise intensity. The lack of difference in HR and RPE between treatments may suggest that AZ did not increase the difficulty of the exercise bout and individuals were able to maintain an optimal intensity in both trials.…”
Section: Discussionmentioning
confidence: 99%
“…This range widens under heat stress when exercise becomes protracted however, as a disassociation develops between %VO2peak, heart rate and perceived exertion. The %V̇O2peak sustained during self-paced cycling is related to the duration or distance of the event, with time trials of 45-60 min conducted at ~85% VO2peak and shorter efforts performed at a greater fraction of maximal aerobic power (132,574,644,732,733,972). Perceived exertion during such trials in the heat is similar and often higher than in cooler conditions (727,731,962,993).…”
Section: Self-paced Exercise In the Heatmentioning
confidence: 99%